Correction: A biocompatible two-photon absorbing fluorescent mitochondrial probe for deep in vivo bioimaging. Issue 6 (26th January 2022) - Lin, Lingmin; He, Zewei; Zhang, Tianfang; Zuo, Yanming; Chen, Xiangfeng; Abdelrahman, Zeinab; Chen, Feihong; Wei, Zhongcao; Si, Ke; Gong, Wei; Wang, Xuhua; He, Sailing; et al.
Abstract : Correction for 'A biocompatible two-photon absorbing fluorescent mitochondrial probe for deep in vivo bioimaging' by Lingmin Lin et al., J. Mater. Chem. B, 2022, DOI: ; 10.1039/d1tb02040d .